2011
DOI: 10.1051/0004-6361/201117263
|View full text |Cite
|
Sign up to set email alerts
|

Polarization properties of OH masers in AGB and post-AGB stars

Abstract: Context. Ground-state OH maser emission from late-type stars is usually polarized and remains a powerful probe of the magnetic field structure in the outer regions of circumstellar envelopes if observed with high angular and spectral resolutions. Observations in all four Stokes parameters are quite sparse and this is the most thorough, systematic study published to date. Aims. We aim to determine polarization properties of OH masers in an extensive sample of stars that show copious mass loss and search for can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 45 publications
(82 reference statements)
8
21
0
Order By: Relevance
“…Recent polarization observations of CSE 1.6 GHz OH masers confirm a regular structure and few milliGauss magnetic field strength in AGB OH maser envelopes (Wolak et al 2012) as found in previous observations. Recent years have also seen an increase in 22 GHz H 2 O and 43 GHz SiO maser observations of Mira variables, OH/IR stars and supergiants.…”
Section: Agb Stars and Supergiantssupporting
confidence: 87%
“…Recent polarization observations of CSE 1.6 GHz OH masers confirm a regular structure and few milliGauss magnetic field strength in AGB OH maser envelopes (Wolak et al 2012) as found in previous observations. Recent years have also seen an increase in 22 GHz H 2 O and 43 GHz SiO maser observations of Mira variables, OH/IR stars and supergiants.…”
Section: Agb Stars and Supergiantssupporting
confidence: 87%
“…However, we emphasize that the 1665/7 MHz OH maser emission originates in inner regions when compared to the 1612 MHz OH maser transition. Therefore, it is expected that magnetic field strength measurements based on the first line to be stronger than the second (Wolak et al 2012). (Vlemmings et al 2002(Vlemmings et al , 2005Herpin et al 2006;Rudnitski et al 2010).…”
Section: Magnetic Field Dependencementioning
confidence: 99%
“…Improvements of spectral resolution up to 0.1 km s −1 enabled detection circularly polarized features in several objects (Zell & Fix 1991), whereas linear polarization was usually weak, if any (Olnon et al 1980). Our recently published polarimetric survey of AGB and post-AGB stars revealed widespread occurrence of polarized OH maser emission (Wolak et al 2012). More than 75% of the objects in the complete sample have polarized features.…”
Section: Introductionmentioning
confidence: 91%
“…The linearly polarized flux density p = (Q 2 + U 2 ) 0.5 , fractional linear polarization, m L = p/I, and polarization position angle, χ = 0.5 tan −1 (U/Q), were derived from the Stokes parameters. The properties of the star sample are given in Wolak et al (2012). In the following we limit the discussion to the sources that have both extreme peaks at 1612 MHz brighter than 10σ, i.e.…”
Section: Observationsmentioning
confidence: 99%